Tumor necrosis factor-alpha inhibitors for the treatment of psoriasis patients with liver cirrhosis: A report of four cases with a literature review - SALMAN, ANDAÇ; SEÇKİN GENÇOSMANOĞLU, DİLEK; ERGUN, SAFİYE ATLAS TÜLİN (MEDKNOW PUBLICATIONS & MEDIA PVT LTD, 2017)
Patients with psoriasis are at an increased risk of developing liver disease due to various factors. The existing data regarding the treatment of psoriasis patients with associated liver cirrhosis is limited. We report four patients of psoriasis with liver cirrhosis who were treated with TNF-alpha inhibitors for a mean duration of 35.4 months. Two patients were treated with etanercept, one with adalimumab and one was treated with both infliximab and etanercept. Three patients tolerated the treatment well without any deterioration of liver disease whereas one died of progressive liver disease. Although large-scale, controlled studies are needed, this case series provides insights regarding the long-term safety of TNF-alpha inhibitors in patients with psoriasis and liver cirrhosis.
Keywords: Adalimumab; cirrhosis; etanercept; infliximab; psoriasis; TNF-alpha inhibitors; CHRONIC HEPATITIS-C; PRIMARY BILIARY-CIRRHOSIS; RHEUMATOID-ARTHRITIS; ETANERCEPT; THERAPY; ANTAGONISTS; DISEASE; GUIDELINES; INFECTION; FIBROSIS